The Redesign of Proposal Seminar Process Using Business Process Modelling and the Devil’s Quadrangle Framework - Wahyuni, Cahyaningtyas Sekar; Fahmi, Mohammad; Trismawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
The proposal seminar is a key academic milestone, yet many institutions still manage it manually, leading to delays, repeated revisions, fragmented documentation, and high administrative workload. Few studies, however, examine lightweight, low-cost approaches for improving such academic workflows without relying on full automation. This study analyses the proposal-seminar process by translating the existing SOP and administrative guidelines into a BPMN model and evaluating its performance using the Devil’s Quadrangle framework. The as-is model reveals issues across all four dimensions, i.e. long cycle times, high process effort, inconsistent documentation, and limited flexibility. A lightweight to-be process is proposed, emphasizing simplification, standardization, and the use of existing digital tools such as Google Forms, shared folders, and templates. Evaluation results show positive improvements across time, cost, and quality, demonstrating that modest interventions can enhance academic administrative processes. The study also offers practical implications, showing that faculties can implement these enhancements immediately using existing resources without additional budget or IT infrastructure. Future work may include quantitative performance measurement and gradual integration of automation to further strengthen process efficiency.